Inter-Regional Trade Mapping in Stock Management, Transport, Infrastructure and Distribution of Strategic Food Commodities toward Province of Bangka Belitung Island, Indonesia - Echo Perdana Kusumah; Dian Prihardini Wibawa (Integrated Journal of Business and Economics (IJBE), 2017)
This study has the primary purpose of mapping examine inter-regional trade on stock management, transportation, infrastructure and distribution of strategic food commodities. Descriptive analysis approach to stock management, transportation, infrastructure and distribution to the survey results emphasized the traders, especially Regional Wholesaler because of the previous research in Pangkalpinang market structure is an oligopoly. In the quantitative analysis oriented, Nearest Neighbor Analysis to explain the distribution pattern of the merchants on the island of Bangka Belitung Province. These studies draw on the field survey conducted by the survey team of students who are competent to carry out the task. The field survey of nearly 200 respondents which include Regional Wholesaler, Local Wholesaler, Main Market Retailers, Traditional Market Retailers and Modern Market Retailers spread across 6 districts and 1 municipality. The study also focused on several commodities including Rice, Sugar and Cooking Oil which not only as the primary needs of Bangka Belitung Islands but also its impact on inflation and general economic welfare. The analysis above is expected to contribute to the literature review which is concerned in the field of economics and policymakers in Province of Bangka Belitung Islands.